Implementation of Sufism Values in Effort in Corruption Prevention and Eradication - Mukhlis Malik (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2019)
The research aims to analyze the implementation of Sufism values to prevent corruption in PT. Telkom Witel Medan. This research uses qualitative methods. In this research, the researcher analyzed module books that were used as a guide for lecturers in PT. Telkom. Besides, the researcher interviewed members of the Board of Prosperity Mosque, namely, the manager of lectures, lecturers, and the management of PT. Telkom Witel Medan. This research shows that the values of Sufism, which is implemented in PT. Telkom Witel Medan has been quite effective in preventing corruption, even though it is not the only determinant. At the national level, this success is evidenced by the achievement of the Best of the best BUMN in the Mental Revolution Award 2018. PT Telkom also won two awards from the Corruption Eradication Commission (KPK) as an Institution with the best Implementation of the State Assets Property Report (LHKPN) 2018 and BUMN with the Best Gratuity Control System in 2018.